2021
DOI: 10.1371/journal.pone.0245057
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety and depression symptoms, the recovery from symptoms, and loneliness before and after the COVID-19 outbreak among the general population: Findings from a Dutch population-based longitudinal study

Abstract: Objectives Examine the effects of the COVID-19 pandemic on the mental health and loneliness in the general population. More specifically, the study focused on prevalence of anxiety and depression symptoms, the extent to which individuals with existing symptoms recovered or not, the prevalence of subtypes of loneliness, and the extent to which loneliness before and during this pandemic was associated with anxiety and depression symptoms. Methods Data was extracted from the longitudinal LISS panel, based on a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
107
2
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 120 publications
(129 citation statements)
references
References 42 publications
17
107
2
3
Order By: Relevance
“…The first emotional reactions may represent feelings of fear, anger, or sadness in response to an unprecedented situation rather than a mental disorder. More fine-grained analyses have showed that mental health problems remained stable or declined throughout the initial lockdown period (Chandola et al, 2020;Daly et al, 2020;Somma et al, 2020;van der Velden et al, 2021;Gonzalez-Sanguino et al, 2020;Wang et al, 2020;Bryan et al, 2020;Hyland et al, 2020;McGinty et al, 2020a), which would be consistent with the notion of a progressive adjustment for managing and overcoming stressful events. It is worth noting that these are findings at a very early stage of the COVID-19 outbreak and different conclusions may hold for the comparisons among rate estimates of mental health conditions in the mid-and long-term.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…The first emotional reactions may represent feelings of fear, anger, or sadness in response to an unprecedented situation rather than a mental disorder. More fine-grained analyses have showed that mental health problems remained stable or declined throughout the initial lockdown period (Chandola et al, 2020;Daly et al, 2020;Somma et al, 2020;van der Velden et al, 2021;Gonzalez-Sanguino et al, 2020;Wang et al, 2020;Bryan et al, 2020;Hyland et al, 2020;McGinty et al, 2020a), which would be consistent with the notion of a progressive adjustment for managing and overcoming stressful events. It is worth noting that these are findings at a very early stage of the COVID-19 outbreak and different conclusions may hold for the comparisons among rate estimates of mental health conditions in the mid-and long-term.…”
Section: Discussionmentioning
confidence: 80%
“…Among the studies tracking longitudinal changes in mental health from before to during the pandemic, some of them have showed increases in the prevalence rate of depression and suicidal ideation (Daly et al, 2020;Niedzwiedz et al, 2020;McGinty et al, 2020b;Novotny et al, 2020;Pierce et al, 2020;Planchuelo-Gomez et al, 2020;Winkler et al, 2020) while others did not report differences above pre-pandemic levels (Kwong et al, 2020;van der Velden et al, 2020) or even decreased estimates (van der Velden et al, 2021). It is worth noting that all but one of the previous studies measured 12 psychological distress or depressive symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies evaluating the general population during the current pandemic found considerably high and increased levels of psychological distress [ 18 , 19 , 21 23 , 25 , 30 , 31 , 81 83 ], potentially related to environmental factors such as quarantine [ 12 , 84 ], socioeconomic effects, and the risk of infection. However, several longitudinal studies did not find an increase in psychological distress in the general population before and during the first months of the pandemic [ 27 29 ]. First studies further differentiating between individuals who have a relative with COVID-19 and those who do not, suggest that having a sick relative causes significantly higher levels of distress [46.7 vs. 27.7%; 79 , 84 , 85 ].…”
Section: Discussionmentioning
confidence: 99%
“…Two prospective studies analyzing the prevalence of anxiety [ 24 ] and depression [ 24 , 25 ] before and after the outbreak in two different samples of the general population each, found an increase in clinically relevant symptoms. Contrary, a Dutch long-term study assessing prevalence of moderate to high levels of anxiety or depression in the general population in November 2019 and March 2020 did not show an increase with rates being 16.9% and 17.0%, respectively [ 26 ] and a later follow-up assessment in June 2020 even revealed a significant decrease to 15.3% [ 27 ]. Findings of a similar Dutch long-term study in older adults and a study comparing serious psychological distress in two samples of the US general population were in line with this [ 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%